2021
DOI: 10.7759/cureus.20189
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment and Level of Satisfaction Among Saudi Hypertensive Patients: A Multi-City Study

Abstract: Background and objectiveHypertension (HTN) is a common disease among patients who visit primary healthcare clinics. Uncontrolled HTN is associated with increased morbidity and mortality; therefore, awareness of its risk factors and adherence to treatment can lead to better control of HTN. In this study, we aimed to determine the level of adherence to treatment and satisfaction among Saudi hypertensive patients. MethodsIn this cross-sectional study, we used an interviewer-administered questionnaire among hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Approximately three quarters of the caregivers are satisfied with the treatment received by the patients and 95% of them consider it easy or very easy to follow the prescribed treatment regimen. This factor seems to be intrinsic to the caregiver as it is consistent with another study focused on adherence and satisfaction in patients with hypertension ( 51 ). Furthermore, dementia is a disease that affects the well-being of caregivers ( 52 ), and the inclusion of the caregivers' perspective is necessary to gain a better understanding of the experience of those living with dementia as included in the study.…”
Section: Discussionsupporting
confidence: 87%
“…Approximately three quarters of the caregivers are satisfied with the treatment received by the patients and 95% of them consider it easy or very easy to follow the prescribed treatment regimen. This factor seems to be intrinsic to the caregiver as it is consistent with another study focused on adherence and satisfaction in patients with hypertension ( 51 ). Furthermore, dementia is a disease that affects the well-being of caregivers ( 52 ), and the inclusion of the caregivers' perspective is necessary to gain a better understanding of the experience of those living with dementia as included in the study.…”
Section: Discussionsupporting
confidence: 87%
“…This result may be because women are more sensitive to disease perception ( 42 ) and adopt more health-seeking behaviors ( 54 , 55 ). Therefore, women have more opportunities to communicate with doctors and receive more medical information about their diseases, which helps build a trusted doctor-patient relationship ( 26 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, when their expectations were not met, they were unsatisfied. A recent study aimed at evaluating medication adherence and satisfaction among hypertensive patients demonstrated that the greater the education, the lower the satisfaction with healthcare services [ 17 ]. Several studies have also found a link between satisfaction and education levels [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients who present with chronic diseases and comorbidities to primary health care are elderly and usually managed by family medicine specialists. Prescription of complex medication regimens is widespread in healthcare centers [16][17][18]. Thus, simplifying medication regimens and educating them in sufficient time and efficient communication help in increasing the satisfaction, perception, and continuity of medication and adherence [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%